Inhibition of AI-2 Quorum Sensing and Biofilm Formation in Campylobacter jejuni by Decanoic and Lauric Acids - Li, Shenmiao; Chan, Kelvin Ka-wan; Hua, Marti Z.; Gölz, Greta; Lu, Xiaonan (Frontiers in Microbiology, 2022)
Campylobacter jejuni is a major bacterial cause of human diarrhoeal diseases worldwide. Despite its sensitivity to environmental stresses, C. jejuni ubiquitously distributes throughout poultry production chains. Biofilm formation mediated by quorum sensing is suggested to be critical to the survival of C. jejuni in agroecosystem. C. jejuni possesses LuxS, the enzyme involved in the production of autoinducer-2 (AI-2) signalling molecules. In this study, two fatty acids, namely decanoic acid and lauric acid, were identified to be effective in inhibiting AI-2 activity of C. jejuni. Both decanoic acid and lauric acid at 100 ppm inhibited ~90% AI-2 activity (P < 0.05) of C. jejuni without bacterial inactivation. The biofilm biomass of two C. jejuni strains was reduced by 10%-50% (P < 0.05) after treatment by both fatty acids, while increased biofilm formation was observed for one C. jejuni strain. In addition, both fatty acids effectively reduced the motility of all tested C. jejuni strains. These findings can aid in developing alternative C. jejuni control strategies in agri-food and clinical settings.